オゾンホール カ ノ タイヨウ シガイ ホウシャ カンキョウ - 竹下, 秀; タケシタ, シュウ; 宮岡, 宏; ミヤオカ, ヒロシ; 江尻, 全機; エジリ, マサキ; 佐々木, 政子; ササキ, マサコ; Takeshita, Shu; Miyaoka, Hiroshi; Ejiri, Masaki; Sasaki, Masako (2001)
P(論文) オゾンホール領域内の太陽紫外放射環境を把握するために, 1999年10月4日から2000年1月31日の現地時刻12時に, 全天太陽UV-B放射量と全天太陽UV-A放射量(以後, それぞれUV-B量, UV-A量と略記)を南極昭和基地で観測した。この観測データを神奈川県平塚市で観測されたUV-B量, UV-A量と比較解析した。昭和基地では12月上旬に最大UV-B量1.73 W/m^2を記録し, この放射量は平塚市の6月中旬と9月上旬のUV-B量に等しかった。昭和基地のUV-B量, UV-A量は平塚市の観測データと比較して変動幅が小さかった。これは, 昭和基地と平塚市では雲形が異なり, 雲形によって太陽紫外放射の遮蔽効果が違うためと考察された。UV-B量から天気の影響を除去するためにUV-B量/UV-A量を求めた。UV-B量/UV-A量と実効オゾン全量との間には強い負の相関が得られた。これよりUV-B量/UV-A量とエアマスを用いて, オゾン全量が推定可能であることを示した。 To analyze characteristics of solar ultraviolet irradiance in the ozone hole region, solar ultraviolet-B (UV-B : 280-315nm) and ultraviolet-A (UV-A : 315-400nm) irradiance at noon were measured from October 4,1999 to January 31,2000 at Syowa Station in Antarctica (69°00′S, 39°35′E). UV-B irradiance measured at Syowa was compared with UV-B irradiance measured at Tokai University, in Hiratsuka, Kanagawa, Japan (35°21′N, 139°16′E). Maximum irradiance of the UV-B at Syowa was measured early in December 1999. It is equal to the maximum irradiance of UV-B measured in the middle of June 1999 and/or early in September 1999 at Hiratsuka. UV-B and UV-A irradiance at Syowa showed less scatter than that at Hiratsuka. This implies that the difference of scatter between irradiance at Syowa and at Hiratsuka may be attributed to the cloud types which appeared over both observation sites, providing different shielding effects of cloud types for UV irradiance. By eliminating the cloud effect by dividing UV-B irradiance by UV-A irradiance (UV-B/UV-A), a high negative correlation was obtained between UV-B/UV-A and the effective ozone amount. By applying this correlation, total ozone amount can be estimated by use of the values of UV-B/UV-A and air mass. departmental bulletin paper